Drivers of skill mismatch among Italian graduates: The role of personality traits - Piero Esposito; Sergio Scicchitano (Global Labor Organization (GLO), 2022)
It is now well accepted that human capital is a heterogeneous aggregate and that non-cognitive skills are at least as relevant as cognitive abilities. In spite of this growing interest in the labour market consequences of personality traits, the relationship between these and educational and skill mismatch is scant. In this paper, we investigate the impact of the five main personality traits (Big 5) on educational and skill mismatch in Italian graduates. To this aim, we use the 2018 wave of the INAPP-PLUS survey, which contains information on skill mismatch, on the Big 5 personality traits, and on a large number of other individual and job-specific characteristics. The empirical analysis takes into account both demand and supply variables mediating the effect of personality on skill mismatch and controls for non-random selection into employment and tertiary education. We find that some personality traits reduce the probability of overeducation, suggesting complementarity between cognitive and non-cognitive skills. In addition, we find a positive effect of conscientiousness on both overeducation and overqualification. The evidence regarding job satisfaction suggests that individuals with high scores for conscientiousness voluntarily decide to be mismatched when this entails higher satisfaction in other dimensions of the job.
Keywords: C25; J24; J31; J82; 330